The Influence of Financial Literacy, Lifestyle, and Social Environment on Impulsive Buying Among Generation Z, with Self-Efficacy as a Mediating Effect - Nesya Tonzani; Tajul 'Ula; Arinal Rahmati (Al Mashaadir : Jurnal Ilmu Syariah, 2026)
This study aims to examine the effects of financial literacy, lifestyle, and social environment on impulsive buying behavior among Generation Z in Langsa City, with self-efficacy serving as a mediating variable. An explanatory research design with a quantitative approach was employed. The study involved 200 Generation Z respondents aged 17–28 years who actively used digital shopping platforms and had online purchasing experience. A multistage sampling procedure was applied by combining purposive sampling and stratified random sampling. Data were collected through a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that social environment had a positive and significant effect on impulsive buying (β = 0.654, t = 5.337, p < 0.001), whereas financial literacy (β = −0.046, t = 0.744, p = 0.457) and lifestyle (β = 0.237, t = 1.874, p = 0.061) did not significantly affect impulsive buying. Likewise, financial literacy (β = 0.361, t = 1.739, p = 0.082), lifestyle (β = −0.049, t = 0.190, p = 0.849), and social environment (β = −0.023, t = 0.085, p = 0.932) did not significantly influence self-efficacy, while self-efficacy also had no significant effect on impulsive buying (β = 0.072, t = 0.791, p = 0.429). Furthermore, the mediation analysis revealed that self-efficacy did not significantly mediate the effects of financial literacy (β = 0.026, p = 0.494), lifestyle (β = −0.004, p = 0.897), and social environment (β = −0.002, p = 0.953) on impulsive buying. The structural model explained 72.2% of the variance in impulsive buying (R² = 0.722), while social environment demonstrated the largest effect size (f² = 0.627). These findings suggest that impulsive buying among Generation Z is primarily shaped by external social influences rather than financial literacy or self-efficacy. From the perspective of Islamic financial management, the findings may serve as an ethical basis for strengthening responsible consumption behavior and financial decision-making, although Islamic financial literacy and Islamic consumption constructs were not directly measured in this study.